The legal statute of the Wilaya delegation of the independent national electoral authority - Amrani, Mourad; Amrani, Mourad; Karana, Adel (Journal of Human Sciences, 2021)
The National Independent Elections Authority has extensions represented by the delegations of WILAYA established by the Council of the Independent Authority.The Algerian legislator has specified the composition of the WILAYA delegation between 3 to 15 members, taking into account the criteria based on the number of municipalities and the distribution of the electoral body, this composition is determined by a decision of the president of the authority after approval by his board, the president of the independent authority appoints the WILAYA delegation coordinator.The delegation of WILAYA under the control of the president of the independent authority exercises the powers devolved to the independent authority in the field of the electoral department of its jurisdiction.